Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: =>3x=10+14=24
=>x=8
b: =>25-30-x=-19
=>-5-x=-19
=>x+5=19
=>x=14
c: =>15-x=12+14=26
=>x=-11
d: =>4x+11-x-34=67
=>3x-23=67
=>3x=90
=>x=30
e: =>-x-14=289-36-289=-36
=>x+14=36
=>x=22
a) 3x=24
x=8
b) 25-30-x=-19
25-30+19=x
14=x
c) 15-x=26
x=-11
d) 4x+11-x-34=67
3x=90
x=30
e) -14-x= -36
x=-14 -36
x= 22
a; \(\dfrac{9}{27}\) + \(\dfrac{7}{-49}\)
= \(\dfrac{1}{3}\) - \(\dfrac{1}{7}\)
= \(\dfrac{7}{21}\) - \(\dfrac{3}{21}\)
= \(\dfrac{4}{21}\)
b; - \(\dfrac{12}{10}\) + \(\dfrac{-25}{30}\)
= - \(\dfrac{6}{5}\) - \(\dfrac{5}{6}\)
= -\(\dfrac{36}{30}\) - \(\dfrac{25}{30}\)
= \(\dfrac{-61}{30}\)
c; \(\dfrac{-20}{35}\) + \(\dfrac{-16}{-24}\)
= - \(\dfrac{4}{7}\) + \(\dfrac{2}{3}\)
= - \(\dfrac{12}{21}\) + \(\dfrac{14}{21}\)
= \(\dfrac{2}{21}\)
d; - \(\dfrac{21}{77}\) + \(\dfrac{10}{-35}\)
= - \(\dfrac{3}{11}\) - \(\dfrac{2}{7}\)
= - \(\dfrac{21}{77}\) - \(\dfrac{22}{77}\)
= - \(\dfrac{43}{77}\)
a ) \(-\frac{13}{30}+\frac{11}{20}-\frac{7}{15}\)
\(=-\frac{26}{60}+\frac{33}{60}-\frac{28}{60}\)
\(=\frac{-26+33-28}{60}=-\frac{7}{20}\)
b ) \(-\frac{5}{72}:\left(\frac{3}{8}.\frac{7}{9}\right)\)
\(=-\frac{5}{72}:\frac{3.7}{8.9}\)
\(=-\frac{5}{72}:\frac{7}{24}\)
\(=-\frac{5}{72}.\frac{24}{7}=-\frac{5}{21}\)
a) \(\frac{-13}{30}+\frac{11}{20}-\frac{7}{15}=\frac{-26}{60}+\frac{33}{60}-\frac{28}{60}=-\frac{21}{60}=-\frac{7}{20}\)
b) \(\frac{-5}{72}:\left(\frac{3}{8}.\frac{7}{9}\right)=\frac{-5}{72}:\frac{7}{24}=-\frac{5}{21}\)
c) \(\frac{-23}{25}.\frac{10}{13}+\frac{-23}{25}.\frac{3}{13}+\frac{-27}{25}\)
\(=\frac{-23}{25}.\left(\frac{10}{13}+\frac{3}{13}\right)+\frac{-27}{25}\)
\(=\frac{-23}{25}+\frac{-27}{25}\)
\(=\frac{-50}{25}=-2\)
a: \(\dfrac{5}{7}=\dfrac{5\cdot11}{7\cdot11}=\dfrac{55}{77}\)
\(\dfrac{9}{11}=\dfrac{9\cdot7}{11\cdot7}=\dfrac{63}{77}\)
b: \(\dfrac{36}{42}=\dfrac{6}{7}=\dfrac{6\cdot9}{7\cdot9}=\dfrac{54}{63}\)
\(-\dfrac{12}{54}=\dfrac{-2}{9}=\dfrac{-2\cdot7}{9\cdot7}=-\dfrac{14}{63}\)
c: \(\dfrac{-11}{30}=\dfrac{-11\cdot4}{30\cdot4}=\dfrac{-44}{120}\)
\(\dfrac{-17}{-40}=\dfrac{17}{40}=\dfrac{17\cdot3}{40\cdot3}=\dfrac{51}{120}\)
d: \(\dfrac{36}{42}=\dfrac{6}{7}=\dfrac{6\cdot3}{7\cdot3}=\dfrac{18}{21}\)
\(\dfrac{-12}{36}=\dfrac{-1}{3}=\dfrac{-1\cdot7}{3\cdot7}=\dfrac{-7}{21}\)
1) (-25).8.(-4).(-125)
= [(-25).4].[(-125).8]
=(-100).(-1000)
=100000
2)30.(5-10)
=30.5-30.10
=30.5-300
=150-300
=(-150)
3) 43.(53-81)+53.(81-43)
=43.53-43.81+53.81-53.43
=(43.53-53.43)+(43.81-53.81)
=0+81.(43-53)
=(-810)
4) Mk chưa biết làm nha
1) (-25).8.(-4).(-125)
= [ (-25) . (-4) ] . [ 8 . (-125) ]
= 100 . (-1000)
= -100 000
2) 30.(-5-10)
= 30 . (-15)
= -450
3) 43.(53-81)+53.(81-43)
= 43 . 53 - 43 . 81 + 53 . 81 - 53.43
= -43 . 81 + 53 . 81
= 81 . ( -43 + 53)
= 81 . 10
= 810
4) (-6)².(-17)+23.(-36)-72.30
= 36 . (-17) + 23 . (-36) - 72. 30
= (-36) . 17 + 23 . (-36) - 72 . 30
= (-36) . ( 17 + 23 ) - 72 . 30
= (-36) . 40 - 72.30
= (-1440 )- 2160
= -3600
# HOK TỐT #
\(\dfrac{21}{36}-\left(-\dfrac{11}{30}\right)=\dfrac{7}{12}+\dfrac{11}{30}=\dfrac{7.5+11.2}{60}=\dfrac{57}{60}=\dfrac{19}{20}\\ ----\\\dfrac{-4}{8}+\left(-\dfrac{3}{10}\right)=\dfrac{-1}{2}-\dfrac{3}{10}=\dfrac{-1.5-3}{10}=\dfrac{-8}{10}=-\dfrac{4}{5}\\ ----\\ \dfrac{7}{12}-\left(-\dfrac{9}{20}\right)=\dfrac{7}{12}+\dfrac{9}{20}=\dfrac{7.5+9.3}{60}=\dfrac{62}{60}=\dfrac{31}{30}\\ ---\\ \dfrac{-2}{5}+\left(-\dfrac{11}{30}\right)=-\dfrac{2}{5}-\dfrac{11}{30}=\dfrac{-2.6-11}{30}=-\dfrac{29}{30}\)
a) 3636:(12x-91) =36
12x-91 = 3636:36
12x-91=101
12x=101+91
12x=192
x=192:12
x=16
b) (x : 23+45).67=8911
(x : 23+45)=8911:67
(x : 23+45)=133
x:23=133-45
x:23=88
x=88.23
x=2024
c) 420+65.4 =(x+175):5+30
420+260=(x+175):5+30
680=(x+175):5+30
(x+175):5=680-30
(x+175):5=650
(x+175)=650x5
(x+175)=3250
x=3250-175
x=3075
d) (32.15):2=(x+70):14-10
480:2=(x+70):14-10
240=(x+70):14-10
(x+70):14=240+10
(x+70):14=250
(x+70)=250.14
(x+70)=3500
x=3500-70
x=3430
e)x-4867=(175.2-50.70):25+23
x-4867=(350-3500):25+23
x-4867=-3150:25+23
x-4867=-126+23
x-4867=-103
x=-103+4867
x=4764
\(\left(\dfrac{7}{30}\right)-\left(\dfrac{11}{36}\right)+\left(\dfrac{23}{30}\right)-\left(\dfrac{25}{36}\right)\)
\(=\dfrac{7}{30}+\dfrac{23}{30}-\left(\dfrac{11}{36}+\dfrac{25}{36}\right)\)
\(=\dfrac{30}{30}-\dfrac{36}{36}\)
\(=1-1\)
\(=0\)